PIK3CA Mutation, Aspirin Use after Diagnosis and Survival of Colorectal Cancer. A Systematic Review and Meta-analysis of Epidemiological Studies. Issue 5 (May 2016) - Paleari, L.; Puntoni, M.; Clavarezza, M.; DeCensi, M.; Cuzick, J.; DeCensi, A.
Abstract: Aims: Regular aspirin use has been associated with inhibition of the whole spectrum of colorectal carcinogenesis, including prevention of metastases and reduced total mortality in colorectal cancer. Preclinical data show that aspirin down-regulates PI3 kinase (PI3K) signalling activity through cyclo-oxygenase-2 (COX-2) inhibition, leading to the hypothesis that the effect of aspirin might be different according to PIK3CA mutational status, but epidemiological studies have led to conflicting results. The aim of this study was to assess the relationship between PIK3CA status and the efficacy of regular use of aspirin after diagnosis on overall survival in colorectal cancer patients. Materials and methods: We identified studies that compared post-diagnosis aspirin efficacy in colorectal cancer patients identified by PIK3CA status. Hazard ratios for overall survival were meta-analysed according to PIK3CA status by inverse variance weighting. A pooled test for treatment by PIK3CA status interaction was carried out by weighted linear meta-regression. All statistical tests were two-sided. Results: The overall effect of aspirin was not significant (summary risk estimate = 0.82; 95% confidence interval 0.63–1.08, P  = 0.16; I 2  = 57%). In PIK3CA mutant disease ( n  = 588), aspirin use reduced total mortality by 29% (summary risk estimate = 0.71; 95% confidence interval 0.51–0.99, P  = 0.04; I 2  = 0%), whereas in PIK3CA wild-type disease ( n  = 4001), aspirin use did not reduce overall mortality (summary risk estimate = 0.93; 95% confidence interval 0.61–1.40; P  = 0.7; I 2  = 80%) ( P interaction = 0.39). There was a beneficial trend for aspirin on cancer-specific survival in PI3KCA mutated subjects (summary risk estimate = 0.37, 95% confidence interval 0.11–1.32, P  = 0.1), albeit with high heterogeneity (Q chi-squared = 3.41, P  = 0.07, I 2  = 70.7%). Conclusion: These findings suggest that the benefit of post-diagnosis aspirin treatment on overall mortality in colorectal cancer may be more marked in PIK3CA mutated tumours, although the low number of studies prevents definitive conclusions. Trials addressing this issue are warranted to assess the efficacy of aspirin in the adjuvant setting. Highlights: Epidemiological data show that aspirin lowers colorectal cancer mortality. A few but not all studies suggest that aspirin is more effective in PIK3CA -positive tumours. We conducted a meta-analysis to determine the consistency of these findings. Aspirin reduced overall mortality by 29% in PIK3CA mutated cancers. Adjuvant trials in PIK3CA mutated colorectal cancers are warranted.